Perancangan Design Game Super Mario Box dengan Pendekatan UI/UX - Geraldo Alfaren; Indra Gunawan (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2024)
Designing a product or application needs to have an effective product design and run systematically. In making interactive products, the interface (User Interface) is required to be easy to understand and must also be created to fulfill the user experience or what is usually called User Experience. One product or application that must implement good UI/UX is a game, the Super Mario Box game. The aim of this research is to create UI and UX designs in designing the Super Mario Box game to achieve a level of comfort and enjoyment for users. Research produces game applications that are designed to be more user friendly and faster to complete. One of them is by providing features and color combinations that are simple and easy to understand.